Development of Thematic Teaching Materials Based on Local Wisdom at Madrasah Ibtidaiyah in Pagaralam City - Amir Rusdi; Amir Hamzah; Tastin Tastin; Nurlaeli Nurlaeli; Denia Widiani (STAI Hubbulwathan Duri, 2023)
The objective of this research and development research is to provide educational resources centred around the Local Wisdom of Pagaralam City, specifically focusing on topic 8